2022
DOI: 10.1108/ijwhm-09-2021-0178
|View full text |Cite
|
Sign up to set email alerts
|

Managing employees’ health, safety and anxiety in a pandemic

Abstract: PurposeThis paper identifies and discusses the strategies adopted by a manufacturing company to manage its national and international employees' anxiety, health and safety with the onset of the COVID-19 pandemic, to fill a current research gap.Design/methodology/approachThis paper uses the qualitative method to identify the strategies employed by a manufacturing company to manage its employees' anxiety, health and safety during the COVID-19 pandemic. Thematic analysis of data from fourteen semi-structured inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…These approaches also parallel best practices (e.g. communication, formulation of policies, education/training and management commitment) that have been identified in managing employee health and safety in more general contexts (Obuobisa-Darko, 2022).…”
Section: Originalitymentioning
confidence: 83%
“…These approaches also parallel best practices (e.g. communication, formulation of policies, education/training and management commitment) that have been identified in managing employee health and safety in more general contexts (Obuobisa-Darko, 2022).…”
Section: Originalitymentioning
confidence: 83%
“…, 2022); healthcare systems acted to protect patients and staff whilst maintaining patient care. The early phase of the pandemic demanded numerous and time-sensitive decisions, which limited opportunities for identifying sources of workers' concerns necessary to efficiently minimise risks to the workforce and maintain optimal performance (Obuobisa-Darko, 2022). Hearing employees' voices and heeding their concerns and suggestions for improvement are important for an organisation navigating its response to a crisis (Cumberland et al.…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, COVID-19 required workplaces to modify practices and procedures to safeguard employees and customers (Mayer et al, 2022); healthcare systems acted to protect patients and staff whilst maintaining patient care. The early phase of the pandemic demanded numerous and time-sensitive decisions, which limited opportunities for identifying sources of workers' concerns necessary to efficiently minimise risks to the workforce and maintain optimal performance (Obuobisa-Darko, 2022). Hearing employees' voices and heeding their concerns and suggestions for improvement are important for an organisation navigating its response to a crisis (Cumberland et al, 2022) while recognising the inherent interconnectedness of employees' well-being and promoting organisational performance (Karanika-Murray and Ipsen, 2022;Ipsen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the COVID-19 pandemic led to the closure of businesses, leading to unprecedented disruption in production, and commercial activities. As a result, organizations were confronted with issues relating to employee health, safety, and anxiety management ( Jungmann & Witthöft, 2020 ; Obuobisa-Darko, 2022 ), supply chain ( Aday & Aday, 2020 ), and workforce management ( Wynne et al, 2021 ). Recent studies have indicated that individuals around the globe have experienced changes in their mental health during the COVID-19 pandemic ( Morin et al, 2021 ; Williams et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Work engagement refers to the harnessing of organization members’ selves to their roles, where individuals employ and express themselves physically, cognitively, and emotionally during the performance of their job roles ( Kahn, 1990 ). Engaged employees, in particular, put in a lot of effort to complete their assigned tasks because they identify with the task ( Obuobisa-Darko, 2022 ; Nkansah et al, 2022 ; Coffie et al, 2023 ). Employees who are engaged with the work have a sense of enthusiastic and effective connection with their work, as they consider the work to be challenging and fulfilling rather than stressful and demanding ( Bakker et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%